Mimicking Breast Carcinoma: Radiologic-Pathologic Correlation in a Rare Case of High-Grade B-Cell Lymphoma - Zakiyah, Rima; Hanum, Aulia; Rosidah, Aris; Putri, Berlian Anggraeni (CV. AKBAR PUTRA MANDIRI, 2026)
Background: Primary breast lymphoma is a rare category of extranodal non-Hodgkin's lymphoma accounting for less than 1% of all non-Hodgkin's lymphoma and less than 0.5% of all breast cancer. It often presents radiologically and clinically as breast cancer leading to delayed diagnosis and inappropriate management. It remains a rare diagnosis that continues to challenge radiologists and clinicians. Case Presentation: A 45-year-old woman presented with a rapidly enlarging mass in her right breast over the past two months. She reported no skin changes, nipple discharge, or associated pain. There was no noteworthy family history or comorbidities. A large, firm, solid mass with skin deformity and attachment to the chest wall was discovered during physical examination. A large, irregular, solid, hypoechoic mass with hypervascularity was discovered by breast ultrasonography. A CT scan of the chest showed several right rib destruction and a soft tissue mass infiltrating the pectoralis muscle. A solid intradural extramedullary lesion from the C4 to L4 vertebrae showing canal stenosis and myeloid edema on a spinal MRI suggested either lymphoma infiltration or dural metastasis. Large lymphoid cells in diffuse proliferation, positive expression of CD45, CD20, and a Ki-67 proliferation index greater than 90% were found in FNAC, histopathology and immunohistochemical examination. The right breast, axilla, vertebrae, and spinal dura mater all showed high FDG uptake on PET-CT. The patient was diagnosed with high-grade B-cell non-Hodgkin lymphoma in the right breast, which had already spread to the bone and spinal cord. The R-CHOP regimen was used to start systemic therapy. Conclusion: Diagnostic vigilance needed in rare cases such as breast non-Hodgkin lymphoma has been emphasized. Clinically, it supports a systematic approach from a deep history and physical examination to reach a correct diagnosis. Radiologically, a homogeneous extensive mass lesion of soft tissue occupying and destroying bone without the common features associated with carcinoma such as skin in-drawing or calcification bears importance for it is not a primary source of epithelial origin. Apart from that, Initial biopsy on atypical breast masses before an operative intervention, and interprofessional collaboration for attaining an appropriate diagnosis and therapy, are crucial. Besides that, it is further expected that radiological awareness of breast lymphoma would eventually lead to better evaluation, diagnosis, management, and unnecessary procedures avoided among the clinicians and radiologists.